Characterization of rpoB Gene Mutations Associated with Rifampicin Resistance in Multidrug Resistant Tuberculosis Patients Co-infected with HIV from Southern India. - Shivaji K Jadhav; Sanjay R Mote; Rajani Katarla (Journal of Drug Resistant Pathogen Research, 2019)
Co-infection of HIV with Mycobacterium tuberculosis is a common event, particularly in developing countries. The emergence and spread of multidrug resistant tuberculosis (MDR-TB) is an increasing public problem in India. The drug-resistant M. tuberculosis strains are posing a significant challenge to TB control. This study used PCR to characterize mutations inside the rifampicin resistance-determining region (RRDR) of the rpoB gene in the rifampicin-resistant M. tuberculosis co-infected with HIV. All the rifampicin-resistant strains had missense mutations. Sequence analysis detected a single or multiple hotspot mutations in the RRDR region of the rpoB gene at codons 516, 512 and 531, in most strains. Furthermore, mutations also occur at codons 512, 514, 517 and 526. The results suggest that hotspot mutations in the rpoB gene are not the sole contributors to MDR-TB co-infected with HIV.
Keywords: rpoB Gene